Keragaan Dan Kelayakan Perakitan Teknologi Budidaya Padi Menggunakan Hazton Di Lahan Rawa Pasang Surut Jambi - jumakir jumakir (Balai Pelatihan Pertanian Jambi, 2023)
The purpose of this study was to determine the economic feasibility and feasibility of rice farming through assembly of Hazton way cultivation technology in tidal swamp land. This assessment was carried out at dry seson in Senyerang Village, Senyerang sub District, West Tanjung Jabung District, Jambi Province in tidal swamp land with sulfuric acid typology and type of puddle of B/C. The Hazton rice cultivation technology package includes quality seeds, superior varieties, jarwo cropping systems, old seedling age of 25-30 HSS, 15-30 seedlings per hill of fertilizer and dolomite use, dosage and fertilization method, water regulation and pest control. Total of five cooperative farmers using the Hazton rice cultivation technology package were included in this assessment. Data were obtained by direct field observation, primary data was collected with Participatory Rural Appraisal approach. Data analysis was done descriptively qualitative and quantitative using partial budget analysis with economic parameters of revenue, income and R/C. The results show that Hazton rice cultivation technology can increase the productivity of 25.58 percent economically to increase the profit of farming by Rp 1.210.000 /ha, meaning that it is financially more profitable than the farmers and feasible to apply. Keywords: Tidal swamp land, Hazton and Economic feasibility